2020
DOI: 10.1002/aet2.10544
|View full text |Cite
|
Sign up to set email alerts
|

Workplace‐based Assessment Data in Emergency Medicine: A Scoping Review of the Literature

Abstract: Objective: In the era of competency-based medical education (CBME), the collection of more and more trainee data is being mandated by accrediting bodies such as the Accreditation Council for Graduate Medical Education and the Royal College of Physicians and Surgeons of Canada. However, few efforts have been made to synthesize the literature around the current issues surrounding workplace-based assessment (WBA) data. This scoping review seeks to synthesize the landscape of literature on the topic of data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(260 reference statements)
0
5
1
Order By: Relevance
“…Thus, the qualifications section may benefit from revisions using validated workplace-based assessment scales including behavioral anchoring descriptions to ensure more consistent rating by evaluators. 7,15,16 Finally, our study found no strong correlation between the qualifications and grades. Previous research has reported grade and rank inflation to occur in up to 60% of SLOEs.…”
Section: Discussioncontrasting
confidence: 67%
“…Thus, the qualifications section may benefit from revisions using validated workplace-based assessment scales including behavioral anchoring descriptions to ensure more consistent rating by evaluators. 7,15,16 Finally, our study found no strong correlation between the qualifications and grades. Previous research has reported grade and rank inflation to occur in up to 60% of SLOEs.…”
Section: Discussioncontrasting
confidence: 67%
“…27,138 It is important to consider data consolidation and distribution with these tools to ensure that feedback is distributed in a timely manner. 137,166 To improve the accessibility of online feedback tools, several platforms have used quick response (QR) codes. 163,167 The use of QR codes to access online feedback forms was found to be user-friendly and resulted in faster completion than paper and online web-based tools not associated with a QR code.…”
Section: Incept Mini-pat Tab Em-hs Cat E-toolsmentioning
confidence: 99%
“…Steps Workplace-basedAssessmentDatainEmergencyMedicine:AScopingReviewoftheLiterature 19 Step 1: Identify the research question…”
Section: Ta B L E 1 Illustrative Example Of a Scoping Reviewmentioning
confidence: 99%